The Injection of Ghrelin (OXE-103) Improves Subacute Concussion Symptom Burden and Quality of Life - Michael Rippee; Michael Wyand; Jamie Chen; Amelia Kirchhoff-Rowald; Suzanne Hunt; Vishal Bansal (Neurotrauma Reports)
Concussions remain the leading form of traumatic brain injury. Despite this, there is a paucity of pharmacologic and evidence-based treatments. The objective of this study was to investigate the benefit of Ghrelin (OXE-103) as a novel treatment for subacute concussion. The study consisted of an open-label treatment arm (OXE-103) with a nontreatment concurrent control arm receiving standard of care (SOC-only). Participants had a documented concussion, within 28 days of injury, and a Post-Concussion Symptom Scale (PCSS) of 20 or more. A total of 19 subjects completed the study: 13 treatments and 6 SOC. Treatment consisted of OXE-103 40 μg/kg twice daily by self-injection for 14 days. Main Outcome Measures were change in PCSS and Quality of Life after Brain Injury–Overall Scale (QOLIBRI-OS). Outcome measures were assessed at days 1, 4, 8, 11, 15, 21, and 44. A secondary outcome was 20% improvement on either which was considered a clinically meaningful response. We found a decrease in PCSS from baseline with OXE-103 (median −34 [interquartile range IQR: −44, −24]) at day 44 versus SOC (median −7 [IQR: −22, 16]) at day 44. We also found an improvement in QOLIBRI-OS from baseline with OXE-103 (median 21 [IQR: 12.5, 50]) at day 44 versus SOC (2 [IQR: –25, 20.8]) at day 44. 85% (95% confidence interval [CI]: 53, 98) of subjects treated with OXE-103 had a clinically meaningful response at day 44 on PCSS versus 33% (95% CI: 4, 78) of subjects in the SOC arm. When looking at improvement in QOLIBRI-OS, 85% (95% CI: 53, 98) of subjects treated with OXE-103 had a clinically meaningful response at day 44 versus 33% (95% CI: 4, 78) in the SOC arm. We conclude that subjects treated with OXE-103 showed improved PCSS and QOLIBRI-OS scores compared to those receiving only standard therapy. We recognize the limitations of this study, including small sample size and lack of randomization. The results indicate that OXE-103 is a potential therapeutic agent to treat patients with ongoing concussion symptoms. A larger, multicenter, randomized, placebo-controlled trial would be an important next step.